Dissociative Identity Disorder in Todd Philips' Joker - Arni Eka Putri Wirjayanti; Ali Mustofa (LPPM Universitas Bumigora Mataram, 2021)
This study examines a dissociative disorder in the film Joker, which aired in 2019 and was directed by Todd Philip. This study aims to show how Arthur Fleck's character becomes someone who suffers from dissociative identity disorder and what factors cause Arthur Fleck who initially looks fine but turns out to have a different side of him. This study uses Sigmund Freud's psychoanalytic theory, which will explain how the conditions of the Id, Ego, and superego in Arthur Fleck are actually the main influences of Arthur's disorder. The results of this study conclude that Arthur Fleck's character immediately changes because of events in his dark past. His past makes Arthur Fleck suffer from disorders such as DID due to the instability of his unstable personality structure.